Pooled Analysis of Rivaroxaban therapy for acute venous thromboembolism in FIRST registry, SWIVTER and DRESDEN NOAC registry - Stephanie Müller; Luise Tittl; Victoria Speed; Lara Roberts; Jignesh Patel; Raj Patel; Roopen Arya; Nils Kucher; David Spirk; Kurtulus Sahin; Jan Beyer‐Westendorf (Research and Practice in Thrombosis and Haemostasis, 2022)
Abstract Background The direct factor Xa inhibitor rivaroxaban is approved for the treatment of venous thromboembolism (VTE), based on the results of large phase III trials. Objectives To confirm rivaroxaban's effectiveness and safety in routine clinical care of patients with VTE. Methods Data were obtained from prospective, noninterventional registries: the FIRST registry (United Kingdom), DRESDEN NOAC registry (Germany), and SWIVTER (Switzerland). Baseline characteristics of these registries and effectiveness and safety outcome rates for the FIRST and DRESDEN NOAC registries were compared. Results A total of 1841 rivaroxaban‐treated patients with acute VTE (57.9% male, 76.6% deep vein thrombosis [DVT]; 23.4% pulmonary embolism ± DVT; median age, 61 years) were included: 1217 from the FIRST registry, 418 from the DRESDEN NOAC registry, and 206 from SWIVTER. Median time between VTE diagnosis and initiation of rivaroxaban was 1.4 ± 1.81 days (25th–75th percentile 1–1; range, 0–15 days). On‐treatment outcome rates for the FIRST and DRESDEN NOAC registries were 0.74 per 100 patient‐years (95% confidence interval [CI], 0.35–1.54) versus 0.96 per 100 patient‐years (95% CI, 0.46–2.01) for VTE recurrence; 1.16 per 100 patient years (95% CI, 0.64–2.09) versus 2.51 per 100 patient‐years (95% CI, 1.58–3.98) for ISTH major bleeding and 1.69 per 100 patient‐years (95% CI, 1.21–2.35) versus 1.73 per 100 patient‐years (95% CI, 1.27–2.36) for all‐cause mortality (intention‐to‐treat analysis), respectively. Conclusion Overall treatment outcomes were consistent with the results of the phase III rivaroxaban trials in VTE treatment, indicating that the use of rivaroxaban offers acceptable treatment results also in routine care. However, we observed significant differences in patient characteristics and management patterns across Switzerland, the United Kingdom, and Germany, limiting direct comparisons of unadjusted outcome event rates between registries.